A time for transformation of governance structures in VET? : A German/Swiss comparison - Hippach-Schneider [Verfasser]; Rieder, Elena [Verfasser] (My University, 2021)
"Digitalisation is affecting vocational education and training (VET) in a multitude of ways and at various levels. In both Switzerland and Germany, stakeholders in VET are responding to the serious technological changes with numerous initiatives and programmes. In this paper, we identify the major differences in policy strategies on state/public policy level, compare some major recommendations and actions of the core stakeholders and identify signs of a changing understanding of their roles in VET. The project basis on a qualitative method approach. There is a large thematic overlap in the topics that actors in Switzerland and Germany address in the context of digitalisation. Nevertheless, it becomes clear that the organisation of the legal governance of the system opens up different scope for action. The similarity of the two VET systems due to their cooperative approach is mitigated by this difference. Within the scope of the project on the role of stakeholders in times of digitalisation, it was possible in particular to identify an intensification of cooperation between the stakeholders combined with a discussion centring on a readjustment of the role of some actors." (Authors' abstract, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S System beruflicher Bildung; S 4.3 Steuerung; S 3.5 Institutionen der Berufsbildungsforschung & -politik; I 2.2.1 Westeuropa; 370; Berufsbildungspolitik; Berufsbildungssystem; Governance; Steuerung; Digitalisierung; Internationaler Vergleich; Bundesrepublik Deutschland; Schweiz